2013
DOI: 10.1097/qad.0b013e32835b3e47
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B and cystatin B in HIV-seropositive women are associated with infection and HIV-1-associated neurocognitive disorders

Abstract: Objective HIV-1-associated neurocognitive disorders (HAND) is triggered by immune activation of brain cells and remain prevalent during progressive viral infection despite antiretroviral therapy. Cathepsins and cystatins are lysosomal proteins secreted by macrophages and microglia, and may play important roles in neuroregulatory responses. Our laboratory has shown increased secretion and neurotoxicity of cathepsin B from in-vitro HIV-infected monocyte-derived macrophages, and increased expression in postmortem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…Thus, it is important to maintain the homeostasis of those enzymes or lysosomal exocytosis. Consistent with our findings, increased cathepsin B release has recently been linked to HIV infectionassociated neuronal death and neurocognitive deficits (76,77). Taken together, these findings suggest important roles of lysosomal exocytosis and cathepsins in neurodegenerative diseases, including HIV/neuroAIDS, and may provide new strategies for development of therapeutics for those diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is important to maintain the homeostasis of those enzymes or lysosomal exocytosis. Consistent with our findings, increased cathepsin B release has recently been linked to HIV infectionassociated neuronal death and neurocognitive deficits (76,77). Taken together, these findings suggest important roles of lysosomal exocytosis and cathepsins in neurodegenerative diseases, including HIV/neuroAIDS, and may provide new strategies for development of therapeutics for those diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Plasma cathepsin B secretion and activity is increased in HIV-seropositive cocaine-users It has been reported that cathepsin B increases in plasma of HIV-seropositive women as compared to HIV seronegative controls (Cantres-Rosario et al 2013). We next asked if cocaine use affected cathepsin B is expression and activity.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma and CSF samples were obtained from a repository of samples of the Hispanic Women cohort followed at the Specialized NeuroAIDS Research Program of the University of Puerto Rico Medical Sciences Campus from 2001-2009 (Wojna et al 2006; Cantres-Rosario et al 2013) following approval by the Institutional Human Subject Review Board (IRB #0720109, 0720102). Patient demographics were as follows: HIV-1 infected women with combined antiretroviral therapy (cART), ages 26-48 years, and nondrug users defined by a urine toxicology screen (n=6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, selected cystatins are now being used as biomarkers to determine the disease severity and to predict patient outcomes (7,8,(38)(39)(40)(41). Subsequently, the replenishment of selected cystatins has been shown to be a promising treatment, specifically in certain types of cancer, to regulate tissue-damaging inflammation and maintain the integrity of the endothelium to prevent tumor metastasis (2,7,9,37).…”
Section: Discussionmentioning
confidence: 99%